The Processes and Practices of Fair Trade : Trust, Ethics and Governance. - Granville, Brigitte (Routledge studies in the modern world economy, 2012)
This book analyzes the factors behind the recent expansion of Fairtrade and questions whether the trust given to the scheme by "ethical" shoppers is warranted. It goes about this assessment by analyzing the claim of ethical shopping and by scrutinizing the specific contribution of the Fairtrade Certification Mark to producer's welfare. This assessment is based on information gathered in a mixture of desk-based research and fieldwork carried out in Argentina, Bolivia, Chile, Peru, Tanzania and South Africa. This book comprises separate chapters written by academics of various backgrounds, who h.